BIOENERGY CONVERSION TECHNOLOGIES: A REVIEW AND CASE STUDY - Al Afif, Rafat; BIKIĆ, Siniša; Radojcin, Milivoj (Journal on Processing and Energy in Agriculture, 2023)
The conversion of organic waste and energy crops into fuel would help society by producing clean fuel from the regenerative feedstock. Industrial biofuels may be non-polluting and sustainable if properly linked with natural ecological cycles. A common method of producing heat and power from bioenergy is biomass gasification. Furthermore, pyrolysis and hydrothermal carbonization are promising thermochemical processes for converting biomass into liquefied fuels and chemicals. Anaerobic digestion is another well-established method that successfully transforms organic waste matter into biogas. The purpose of the study is to review current bio-energy conversion technologies and to provide quantitative data and interpretation of the heating value, proximate and elemental analysis, and product yields specific to bioenergy recovery from some selected biomass materials such as olive mill waste and cotton stalks.  Moreover, some products from the conversion (e.g. biochar from pyrolysis) can be used as a soil additive to recover nutrients and carbon in the soil. The latter can additionally act as water storage. Therefore, utilizing biomass has the potential to be a significant source of energy and an opportunity to reduce environmental issues and financial costs. This study contributes to the needed understanding of energy derived from thermal and biological conversion products of biomass. In this context, according to the characteristics of different kinds of biomass, appropriate utilization methods should be applied to produce bioenergy to realize environmental, economic and energy benefits. The study concluded with some comments on the future potential of these processes.
Keywords: Biomass; bioenergy technologies; biofuels